The Impact of Mindfulness Training on Anxiety and Self-Regulation among Primary School Children - Ambara, Didith Pramunditya; Septiari, Ni Kadek; Listyana, I Gusti Agung Ayu Putu; Rahayu, Ni Komang Ari (Mimbar Ilmu, 2025)
Addressing children’s emotional well-being is crucial for fostering healthy psychological development and optimizing their capacity to thrive in academic settings. However, traditional classroom routines often overlook the role of self-awareness and emotion regulation, especially for younger learners. This study aims to analyze the impact of a mindfulness-based intervention on reducing anxiety and improving self-regulation among primary school children. A quasi-experimental design was employed, involving students who were assigned to either an experimental group receiving mindfulness training or a control group with no such intervention. Anxiety and self-regulation were measured using validated psychological scales before and after the intervention. Multivariate analysis of variance (MANOVA) was used to assess the overall effect of the mindfulness program on both dependent variables. The results revealed that students who underwent mindfulness training demonstrated significantly lower levels of anxiety and improved self-regulation compared to the control group. The findings suggest that mindfulness practices help children develop greater emotional awareness, calmness, and behavioral control, contributing to their overall psychological resilience. This study underscores the value of incorporating structured mindfulness programs into early education to support both emotional and behavioral development.